The Ultimate Price - Owolabi, S S (Rasmed Publications Ltd, 2005)
Bala Amodu became an accomplished pick pocket at a tender age and before adulthood he had graduated to armed robbery and ruthless killing. Bala and his partner, Liman got their wealth through all the evil acts one can mention on this earth but both of them together with their family members pay a price which you need to find out in this book.
Keywords: Juvenile Fiction; Mystery; The Ultimate Price